2019
DOI: 10.1111/1365-2478.12829
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different clay minerals on the anisotropy of clay matrix in shale

Abstract: Although clay is composed of disconnected anisotropic clay platelets, many rock physics models treat the clay platelets in shale as interconnected. However, the clay matrix in shales can be modelled as anisotropic clay platelets embedded within a soft isotropic interplatelet region, allowing the influence of disconnected clay platelets on the elastic properties of the clay matrix to be analysed. In this model, properties of the interplatelet region are governed by its effective bulk and shear moduli, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Sayers (2013b) demonstrated that the elastic properties of organic-rich shales can be reasonably described by this model using elastic stiffnesses of kerogen as a soft interplatelet region. On the other hand, the model assumes that the spatial distribution of clay platelets as defined by a two-point correlation function has the same aspect ratio as the clay platelets (Sayers and den Boer, 2019). This may not be a reasonable assumption for some shale rocks, however, as demonstrated by Ponte Castaneda and Willis (1995), the effect of the spatial distribution of the inclusions on the effective modulus tensor is relatively small.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Sayers (2013b) demonstrated that the elastic properties of organic-rich shales can be reasonably described by this model using elastic stiffnesses of kerogen as a soft interplatelet region. On the other hand, the model assumes that the spatial distribution of clay platelets as defined by a two-point correlation function has the same aspect ratio as the clay platelets (Sayers and den Boer, 2019). This may not be a reasonable assumption for some shale rocks, however, as demonstrated by Ponte Castaneda and Willis (1995), the effect of the spatial distribution of the inclusions on the effective modulus tensor is relatively small.…”
Section: Modelmentioning
confidence: 99%
“…First, clay platelets are assumed to consist of muscovite or ideal kaolinite, whose properties are based on the best-fitting TI approximation of theoretical calculations of Militzer et al (2011). Muscovite properties were used for most of samples since muscovite is both structurally and compositionally similar to the clay mineral illite, thus may be expected to have similar elastic properties (Katahara, 1996;Sayers & den Boer, 2019;Tosaya, 1982), while ideal kaolinite properties were used for Norwegian Sea shale because it is dominated by kaolinite. Although the assumption gave reasonable results, actual clay mineral properties, which have not been measured experimentally, might be largely different from the theoretical calculations, and clay platelets could actually consist of multiple minerals (or there may be domains of different clay minerals).…”
Section: Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…make rocks more compliant and weaker with increasing phyllosilicate content (e.g., Nishizawa & Kanagawa, 2010;Sayers & den Boer, 2019;Sone & Zoback, 2013a). Phyllosilicates are also abundant in fault rocks and are believed to impose critical limits on the strength of crustal faults zones.…”
mentioning
confidence: 99%